Improving access to syphilis screening among unhoused people in Yolo County - Jenna Kupa; Ren Bruguera; Nadia Agnoli; Alicia Agnoli; Liliana Melgoza; Anna Portnoy; P. Suzanne Portnoy (University Library System, University of Pittsburgh, 2024)
Background: This study aimed to increase syphilis screening rates amongst unhoused residents of Yolo County, California, through the implementation of plan-do-study-act (PDSA) cycles. Yolo County has a strategic goal to eliminate congenital syphilis cases. Homelessness is a known risk factor for syphilis.  Methods: The primary researcher was embedded in a street medicine team. Using quality improvement tools like stakeholder interviews, workflow diagrams, and best practices from literature, we outlined the team's workflow for syphilis screening and developed ideas to improve uptake and expand capacity. The most effective cycle implemented gift card incentives for syphilis screening. During the patient intake we offered the option to receive a syphilis test, informing the patient of the gift card incentive.  Results: Prior to gift card incentives, the team screened 1.6 patients on average per clinic for a total of 30 patients screened in April to June of 2022. After the gift card incentive was implemented, the team screened 3.0 patients on average per clinic, screening a total of 223 patients from July 2022 to May 2023. The intervention produced an 87.5% increase in screening rates (P=0.0094). The data showed a significant increase in syphilis testing upon implementing the gift card incentive program. Conclusion: These findings contribute to evidence supporting the use of patient incentives for public health prevention measures. This model could be applied to other populations to increase health screening participation. More research is needed on the effect of gift card incentives on confirmatory testing and treatment rates for syphilis.